Enhancing green innovation and financial performance: the role of stakeholder pressures and green dynamic capabilities - Tjatur Widyantoro; Toto Rusmanto; Dezie Leonarda Warganegara; Asnan Furinto (Frontiers in Climate)
The present study focuses on stakeholder pressures and the green dynamic capabilities of achieving green innovation and financial performance in various sectors in Indonesia. Data were collected from 120 top management representing their companies involved in this study, and path analysis was applied to test the hypothesis. The study results reveal that stakeholder pressures strengthen organizational green dynamic capabilities and innovation. Moreover, the study finds that stakeholder pressures significantly and positively predict green innovation through green dynamic capabilities and corporate financial performance through sequential mediation involving both green dynamic capabilities and green innovation. This study underscores the significance of green initiatives across various sectors, positioning them as essential components of corporate strategy in the modern business landscape.